Xanthine Oxidase and Lipid Peroxidation Inhibition of Taiwan Folkloric Medicine Factors Affecting Rhus semialata var. Roxburghiana Activities against Xanthine Oxidase and Ferrous Iron-induced Lipid Peroxidation on Mice Liver Mitochondria - Tsai, Po-Wei; Lin, Pei-Chin; Yang, Ling-Ling; Liao, Ai-Ho; Wang, Bo-Cheng; Wu, Ming-Shun (Indian Journal of Pharmaceutical Education and Research, 2020)
Background: Gout, a disease characterized by recurrent inflammatory for urate deposit from overactive xanthine oxidase, is common among Taiwanese. Rhus semialata var. roxburghiana (RSR) grows wildly in Central Mountain of Taiwan and used by aboriginal Taiwanese as traditional medicine for gout and hepatitis. Methods: In this study, the factors such as variations in RSR extracts in terms of geographical sources, aerial parts and extraction solvents were investigated for antioxidant capabilities, phytochemical analysis and inhibitory effects against xanthine oxidase and lipid peroxidation using ferrous ion as ROS inducer on mice liver mitochondria. Results: The results showed that ML-n-hexane and NS-acetone gave the maximum XO inhibitions (IC50=16.74±0.74 μg/mL) and LPO inhibitions (IC50=8.40±0.35 μg/mL) in the liver mitochondria of mice, respectively. And ML-n-hexane and NS-acetone contained phenolic and flavonoids compounds for its potential target components against XO and LPO in this study. Conclusion: Overall, RSR could lead to a medicinal potential as a suitable candidate for the development of a natural anti-gout and liver damage protective agent that have yet to be conducted.
Keywords: Rhus semialata var. Roxburghiana extracts; Geographical source; Xanthine; oxidase inhibitor; Free radical scavenging; Liver mitochondria LPO inhibitor